Identificación de la cafeína aislada de las hojas de Ilex inundata Poepp. Ex Reissek por sus características fisicoquímicas y espectrometría UV - Córdova Alvis, Paulo Sergio (2022)
Alkaloids have been the subject of study due to their great bioactive properties for the benefit of human health. Within this group of compounds is caffeine, a pseudoalkaloid derived from purine bases, considered an energy stimulant, analgesic, vasoconstrictor and pain reliever head. The objective of the study was to characterize the alkaloid isolated from the plant species Ilex inundata, of the Aquifoliaceae family. The samples were collected on the banks of the Nanay River, located in the university city of Zungarococha, San Juan Bautista district, Maynas province, Loreto region. Ethanol, magnesium oxide as inclusion reagent, 10% sulfuric acid to separate and chloroform to purify were used to extract the alkaloid. The purified product was identified and characterized by determining its physicochemical parameters and by UV-visible spectrometry. The results were: yield 1.431%, melting point 238ºC, sublimation point 178ºC, Rf values run in [chloroform: ethanol] solution was 57, in [acetone: chloroform: n-butanol and 25% ammonium hydroxide solution %] was 78 and in ethyl acetate: methanol and acetic acid solution it was 41, the molecular weight was 194.227 g/mol and the maximum wavelength in methanol was 273 nm. It is concluded that the leaves of Ilex inundata contain caffeine, and that the species could be a promising source to obtain this alkaloid for use in the pharmaceutical industry.